A Systematic Approach to the Design and Implementation of Clinical Informatics Fellowship Programs - Lingham, Veena; Chandwarkar, Aarti; Miller, Michael; Baker, Carrie; Genes, Nicholas; Hellems, Martha; Khanna, Raman; Mize, Dara; Silverman, Howard (Applied Clinical Informatics, 2023)
Clinical Informatics (CI), a medical subspecialty since 2011, has grown from the initial four fellowship programs accredited by the Accreditation Council for Graduate Medical Education (ACGME) in 2014 to more than 50 and counting in the present day. In parallel, the literature guiding Clinical Informatics Fellowship training and the curriculum evolved from the original core content published in 2009 to the more recent CI Subspecialty Delineation of Practice and the updated ACGME Milestones 2.0 for CI. In this paper, we outline this evolution and its impact on CIF Curricula. We then propose a framework, specific processes, and tools to standardize the design and optimize the implementation of CIF programs.
Keywords: Clinical Informatics; Professional training; Education; Curriculum Development; Training requirements